AB0295 The recall survey: data from a multicenter educational event on patients with ra. (15th June 2017) - Sedie, A Delle; Filippucci, E; Epis, O; Macchioni, P; Tropea, S; Bonali, C; Canzoni, M; Iagnocco, A
Abstract : Background: Ultrasound (US) is able to show subclinical synovitis in patients (pts) with rheumatoid arthritis (RA) who are in clinical remission (CR); this has been proposed as a predictive factor for both clinical flares and progression of the structural damage in CR pts. Objectives: To investigate the US characteristics of RA pts presenting either CR or low disease activity (LDA). Methods: In 2015 an educational event focused on the added value of US in RA pts was held in 22 rheumatology centers in Italy. After a brief presentation on the evidence of US added value for the clinician given by expert sonographers (rheumatologists with a special interest in US that were performing US as their usual activity for many years), in every center, the local rheumatologists provided RA pts to be examined by US. All the US machines were identical both for type (Logiq E R7, General Electrics, with a 4.2–13 MHz linear probe) and settings (both for grey-scale and power Doppler (PD)). Pts signed an informed consent and a brief history of them was collected by the local rheumatologists (previous and current therapy, DAS28, HAQ score). The US examination was performed bilaterally on wrists, MCP and MTP joints, looking for synovitis (effusion, synovial proliferation and PD signal) and bone erosions. The positive findings were scored according to a 0–3 score for synovitis components and presence/absence for erosions; the number and size of the largest erosion was also registered. Results: Demographic and descriptive data of the 433 pts examined are reported in Table I. Pts were divided on the basis of the DAS28 result. Statistically significant differences in age and disease duration were registered between the group in CR and the group with DAS28≥3.2 (p=0, 019 and p=0, 012, respectively), while no differences were found for HAQ or MTX use. Higher positivity of findings, regardless which was the score, was present in LDA group for effusion, synovial proliferation and PD signal. Significant differences were seen between CR and LDA group for effusion (general, MCP and MTP joints; p=0, 011, p=0, 026, p=0, 017 and p=0, 013, respectively), PD positivity (general, wrist, MCP and MTP joints; p=0, 006, p=0, 023 and p=0, 05, respectively) and erosions (p=0, 002), with higher positivity for pts in LDA. Conclusions: The US assessment in this large cohort of RA pts showed frequent positive findings both in the CR and in the LDA group, confirming the results from previous studies. US is a useful imaging tool for the detection of subclinical joint abnormalities in RA. Disclosure of Interest: None declared